Synthesis and characterization of novel palmitic acid conjugated tetrapeptide as a new active molecule for wound treatment - Md Fadilah, Nur Izzah (2020)
Therapeutic drugs have generated a great interest in pharmaceutical field for their beneficial effects towards wound treatment. However, clinical applications of drugs as therapeutic agent such as antiseptic are limited due to high toxicity and side effects including irritation and itching caused by the drug host. Therefore, a new sequence of peptide was designed, characterized and explored to find out its potential application in wound treatment. A novel fatty acid conjugated tetrapeptide known as palmitic acid conjugated glycineaspartic acid-proline-histidine (Palmitoyl-GDPH) was synthesized using Solid Phase Peptide Synthesis (SPPS) method. It was determined by High Performance Liquid Chromatography (HPLC) with high percentage purity of 98.6%. Screenings of its biological activities were done by in vitro studies using enzymatic and cell based assays. From the results, it was evident that Palmitoyl-GDPH gave higher percentage activity of collagen enzyme (80.00 ± 2.22%). Besides, the EC50 of Palmitoyl-GDPH towards nitric oxide (NO) scavenging effect was low (1.05 ± 0.10 mg/mL) which shows a good antiinflammatory compound. This peptide was further evaluated on normal human dermal fibroblast (NHDF) cell. Accordingly, the percentage of cell viability remained above 90% throughout the Palmitoyl-GDPH treatment (p<0.01) and the cells did not showed cytotoxicity up to concentration of 100 μg/mL. Meanwhile, the cells were grown and showed proliferation in time-dependent manner (72 h). From the mimic wound in vitro study, the Palmitoyl-GDPH treated cells were significantly promoted with high percentage of NHDF migration from 32.10 ± 2.74% to 98.39 ± 2.79% and reached full gap closure faster at 100 μg/mL during 48 h treatment (p<0.01) compared to standard drug. Through a combination of cell proliferation and cell migration, Palmitoyl-GDPH was comparable to be a therapeutic agent for skin wound healing. The results from in vivo study revealed that Palmitoyl-GDPH treated wound displayed significantly 100% wound closure at day 18 with smooth and flat appearance compared to non-treated and standard drug (tetracycline) groups as evident by macroscopical analysis. Histological examination of the wound treated by Palmitoyl-GDPH presented no scar, fewer inflammatory cells, more hair follicles, fibroblast and blood vessels, and also extensive collagen deposition that were equivalent to normal skin tissue group. The epidermis and dermis thickness of Palmitoyl-GDPH treated wound were 46.99 ± 3.49 μm and 983.52 ± 8.41 μm, respectively which were comparable to skin layer of intact skin tissue and thus represented good epithelialization progress. At the end of the experimental time, rats were sacrificed and blood samples were collected and tested for hematology and biochemistry changes. The results indicated that Palmitoyl-GDPH treated group had intermediate levels of red blood cells and platelet counts while the values showed no significant difference compared to normal rats (p>0.05). Overall from the blood tests, there were no significant difference (p>0.05) and no systemic adverse effects on the animals following wound treatment with Palmitoyl-GDPH. These findings revealed the potential of Palmitoyl-GDPH to be used as an effective therapeutic agent for wound treatment through reduced wound area, increased re-epithelialization, enhanced collagen deposition and diminished scar formation.